2014
DOI: 10.1002/mgg3.68
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum and genotype‐phenotype correlations in a large French cohort of MYH9‐Related Disorders

Abstract: MYH9-Related Disorders are a group of rare autosomal dominant platelet disorders presenting as nonsyndromic forms characterized by macrothrombocytopenia with giant platelets and leukocyte inclusion bodies or as syndromic forms combining these hematological features with deafness and/or nephropathy and/or cataracts. They are caused by mutations in the MYH9 gene encoding the nonmuscle myosin heavy chain II-A (NMMHC-IIA). Until now, at least 49 MYH9 mutations have been reported in isolated cases or small series b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 39 publications
(59 reference statements)
7
62
0
1
Order By: Relevance
“…However, recent investigations showed that this mutation is associated with not only sensorineural hearing loss but also macrothrombocytopenia and neutrophil inclusions. [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigations showed that this mutation is associated with not only sensorineural hearing loss but also macrothrombocytopenia and neutrophil inclusions. [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss was early onset and severe in the DIAPH1 R1213* cases but develops in only 35% of MYH9-RD cases, typically after 10 years of age. 10 Cataract and nephropathy are reported in 5% and 21% of MYH9-RD cases, respectively, 10 but were absent in the DIAPH1 R1213* cases. Interestingly, mild neutropenia was frequently observed in the DIAPH1 R1213* cases (Table 1).…”
Section: Org Frommentioning
confidence: 97%
“…It has been proposed that the platelet phenotype associated with some MYH9, 13,14 ACTN1, 7 and TUBB1 15 variants results from aberrant cytoskeletal rearrangements during proplatelet formation, leading to altered platelet production. Cytoskeletal dysfunction may also underlie phenotypes such as hearing loss, cataract, and glomerulopathy associated with some variants in MYH9, 10,16 and periventricular nodular heterotopia and otopalatodigital syndromes associated with some variants in FLNA. 8 Here, we extend the repertoire of MTP by reporting the discovery of a new dominant syndromic disorder of platelet formation.…”
Section: Introductionmentioning
confidence: 99%
“…and sometimes hearing loss and cataract) [1,2]. The bleeding tendency is mild to moderate and easy bruising, epistaxis and menorrhagia are the most prevalent symptoms [3].…”
Section: Myh9-related Disorders (Myh9-mentioning
confidence: 99%